Evaluation of Toric Intraocular Lenses in Patients With Low Degrees of Astigmatism. Issue 5 (September 2015) - Levitz, Lewis; Reich, Joe; Roberts, Kate; Hodge, Chris
<x xml:space="preserve">Abstract</x> Purpose This study aimed to describe the efficacy of toric intraocular lenses (IOLs) in patients with low degrees of corneal astigmatism. Design Retrospective case series was undertaken. Methods Patients with low amounts of corneal astigmatism who were treated with either a toric monofocal lens (SN6AT2 Toric, n = 76) or a toric multifocal lens (SND1T2 +3.00, n = 44) were reviewed. Eyes were evaluated preoperatively and 3 months postoperatively. Refraction and visual outcomes were monitored. Results Patients (69.7%) in the monofocal toric group obtained refractive cylinder less than 0.25 diopters (D) compared with 70.5% of the multifocal toric group. Both toric groups showed a statistically significant reduction in refractive cylinder after surgery (P = 0.001). Monofocal (66.7%) and multifocal (68.2%) toric patients achieved uncorrected distance visual acuity of 20/20 or better. Conclusions This represents the first article to investigate the use of low-power toric IOLs in patients with less than 1.25 D of corneal cylinder. Before the development of low-power toric IOLs, patients with low to moderate amounts of astigmatism required concurrent intraoperative adjustments or additional forms of treatment to benefit from cataract and IOL surgery. Evidence suggests that the toric T2 IOL now removes this barrier, providing consistent, accurate refractive and astigmatic results, and enables these patients to achieve excellent outcomes with a single treatment across IOL platforms. Larger studies will help to consolidate our results.